Challenges and Controversies in Human Mesenchymal Stem Cell Therapy - Barbara Lukomska; Luiza Stanaszek; Ewa Zuba-Surma; Pawel Legosz; Sylwia Sarzynska; Katarzyna Drela (Hindawi Limited, 2019)
Stem cell therapy is being intensely investigated within the last years. Expectations are high regarding mesenchymal stem cell (MSC) treatment in translational medicine. However, many aspects concerning MSC therapy should be profoundly defined. Due to a variety of approaches that are investigated, potential effects of stem cell therapy are not transparent. On the other hand, most results of MSC administration in vivo have confirmed their safety and showed promising beneficial outcomes. However, the therapeutic effects of MSC-based treatment are still not spectacular and there is a potential risk related to MSC applications into specific cell niche that should be considered in long-term observations and follow-up outcomes. In this review, we intend to address some problems and critically discuss the complex nature of MSCs in the context of their effective and safe applications in regenerative medicine in different diseases including graft versus host disease (GvHD) and cardiac, neurological, and orthopedic disorders.